The effect of relative age on some performance characteristics in young volleyball players - Akarçesme, C.; Aytar, S. H. (Journal of Education and Training Studies, 2018)
It has been evaluated in the literature that different maturation levels exist in the same chronological age and this may be an advantage for athletic performance. The aim of this study was to examine the performance characteristics of young male and female volleyball players in the same chronological age according to their relative age.